Students' Perspectives: How Will COVID-19 Shape the Social Determinants of Health and Our Future as Public Health Practitioners?. (December 2020) - Asfaw, Eliyas K.; Guo, Emily S.; Jang, Sarah S.; Komarivelli, Swathi R.; Lewis, Katherine A.; Sandler, Claire B.; Mehdipanah, Roshanak
We are the next generation of public health practitioners. As public health students, we acknowledge that the COVID-19 (coronavirus disease 2019) pandemic will continue to fundamentally alter the field that we are preparing to enter. We will be the first wave of public health professionals whose education is being shaped by this pandemic. For decades to come, we will be working to address the impacts of this pandemic. In this commentary, we are lending our voice to discuss and highlight the importance of considering the intersections of various determinants of health and COVID-19, including education, food insecurity, housing instability, and economic hardship. We provide a discussion on what is being done across the United States in attempts to reduce the growing health inequities. As the next generation of public health leaders, we believe that only by investing in these issues can we begin to address the social and economic impact of the COVID-19 pandemic.